Structural and mechanical stability, lattice dynamics and electronic structure of the novel CrVZ (Z = S, Se, & Te) half-Heusler alloys. (December 2020) - Javed, Mehreen; Sattar, Muhammad Atif; Benkraouda, Maamar; Amrane, Noureddine
Highlights: Novel HH CrVZ (where Z = S, Se & Te) alloys are chemically, thermodynamically, mechanically stable compounds. The HH CrVSe and CrVTe alloys are vibrationally stable whereas HH CrVS shows soft modes. HH CrVZ (where Z = S, Se & Te) alloys are half-metallic ferromagnetic materials. HH CrVZ (where Z = S, Se & Te) alloys are 100% spin-polarized and follow the Slater-Pauling rule and have a magnetic moment of 1 μ B . The HH CrVSe has a direct bandgap 1.07 eV and half-metallic gap of 0.44 eV calculated by the mBJ potential. HH CrVZ alloys have the lower values of Seebeck coefficient and Power factor. Abstract: To meet energy demand, half-Heuslers (HH) are proved to be a cost-effective and energy-efficient choice for advanced spintronic and energy storage applications. The structural, electronic, magnetic, vibrational, elastic, thermodynamic and thermoelectric properties of the innovative HH CrVZ (where Z = S, Se, & Te) alloys are studied by using density functional theory (DFT). All materials are found to be magnetically active with 100% spin polarization where partially filled 3 d -orbitals of Cr confirm the major contribution to the magnetic moment. The ferromagnetic (FM) state is observed to be the most energetically stable state among the non-magnetic (NM) and antiferromagnetic (AFM) states for all the HH CrVZ alloys with their optimized lattice parameters ranging from 5.47 Å to 6.00 Å. The HH CrVSe alloy is found to have the lowest direct bandgap ( E B G ) of 1.07 eV with a comparatively highest half-metallic gap ( E H M ) of 0.44 eV, due to the d-d hybridization. Our calculated cohesive ( E C ) and formation ( E f ) energies indicate the chemical and thermodynamic stability of the studied HH CrVZ alloys. The phonon dispersion curves for the HH CrVSe and CrVTe alloys show that they are vibrationally stable while HH CrVS alloy shows soft modes with imaginary frequency due to the small ionic size of the S-ion. The calculated Cauchy pressure, Pugh and Poisson ratio prove that all studied compounds are hard, elastically brittle, anisotropic, and mechanically stable. The temperature fluctuations for specific heat (CV ), Entropy (S) and Free Energy (F) follows the Quasi-harmonic Debye model with expected Dulong-petit limit 75 J/mol/K. The thermoelectric investigations although show the lower values of the Seebeck coefficient and power factor. Our investigated half-metallic HH CrVZ alloys can be the potential contenders for the spintronic applications.